2006
DOI: 10.1021/ja0659830
|View full text |Cite
|
Sign up to set email alerts
|

Redox-State-Dependent Complex Formation between Pseudoazurin and Nitrite Reductase

Abstract: Bacterial copper-containing nitrite reductase catalyzes the reduction of nitrite to nitric oxide as part of the denitrification process. Pseudoazurin interacts with nitrite reductase in a transient fashion to supply the necessary electrons. The redox-state dependence of complex formation between pseudoazurin and nitrite reductase was studied by nuclear magnetic resonance spectroscopy and isothermal titration calorimetry. Binding of pseudoazurin in the reduced state is characterized by the presence of two bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…It has been shown that this substitution does not affect the structure significantly 18 or influence the binding to Nir. 20 Attempts to determine a dissociation constant for the complex of NiR and Paz by NMR titration experiments have been hampered until now by the size of this complex. 20 A full titration of NiR into ZnPaz was obtained using perdeuterated Paz in combination with TROSY.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that this substitution does not affect the structure significantly 18 or influence the binding to Nir. 20 Attempts to determine a dissociation constant for the complex of NiR and Paz by NMR titration experiments have been hampered until now by the size of this complex. 20 A full titration of NiR into ZnPaz was obtained using perdeuterated Paz in combination with TROSY.…”
Section: Resultsmentioning
confidence: 99%
“…4). This region of the protein structure has been shown to serve as the recognition site for a CuNIR for four of the five other pseudoazurins [14,[37][38][39][40]. A complete pathway for denitrification has been identified in the annotated S. meliloti genome, including a gene encoding a putative CuNIR [16] and a sequence alignment of the S. meliloti and A. faecalis CuNIRs using LALIGN [41] reveals that they share 82% sequence identity.…”
Section: Structure Of the Electrostatic Surfacementioning
confidence: 99%
“…1b) [5]. In addition, the ligated to Cu(II) His81 interacts weakly with the side chain of Met16 residue, which is in the close vicinity of the PAz-NiR binding site [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent NMR spectroscopic studies revealed that Ala15 could be involved in the formation of the AcPAz-NiR complex [14,15]. Therefore, an investigation of the His81-Met16 interaction became necessary [36] in order to understand its role in modulation of the electronic structure and reactivity of the blue copper(II) site.…”
Section: Introductionmentioning
confidence: 99%